2009
DOI: 10.1002/bit.22343
|View full text |Cite
|
Sign up to set email alerts
|

A two‐phase partitioning airlift bioreactor for the treatment of BTEX contaminated gases

Abstract: This investigation characterizes a novel 11 L airlift two-phase partitioning bioreactor (TPPB) for the treatment of gases contaminated with a mixture of benzene, toluene, ethylbenzene, and o-xylene (BTEX). The application of the TPPB technology in an airlift bioreactor configuration provides a novel technology that reduces energy intensity relative to traditional stirred tank TPPB configurations. The addition of a solid second phase of silicone rubber beads (10%, v/v) or of a liquid second phase of silicone oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…The cell mass was maintained in the range of 9-11 g/L for 10 days and the fluctuation of cell mass may be due to intermittent loading of the compound for 10 h a day and 5 days a week to simulate an actual industry operating schedule. Interestingly, other research using polymers as a second phase instead of an organic solvent in a TPPB fed with a mixture of benzene, toluene, ethylbenzene and o-xylene to a microbial consortium showed biological steady state from 300 to 400 h of operation with a collective maintenance coefficient of 0.0103 h -1 at biological steady state [9]. We could prolong the biological steady state to about 1 month without medium change by refining medium formulation with the same microorganism, A. xylosoxidans Y234, for benzene degradation in a TPPB [32].…”
Section: Dynamics Of the Maintenance Coefficientmentioning
confidence: 95%
See 1 more Smart Citation
“…The cell mass was maintained in the range of 9-11 g/L for 10 days and the fluctuation of cell mass may be due to intermittent loading of the compound for 10 h a day and 5 days a week to simulate an actual industry operating schedule. Interestingly, other research using polymers as a second phase instead of an organic solvent in a TPPB fed with a mixture of benzene, toluene, ethylbenzene and o-xylene to a microbial consortium showed biological steady state from 300 to 400 h of operation with a collective maintenance coefficient of 0.0103 h -1 at biological steady state [9]. We could prolong the biological steady state to about 1 month without medium change by refining medium formulation with the same microorganism, A. xylosoxidans Y234, for benzene degradation in a TPPB [32].…”
Section: Dynamics Of the Maintenance Coefficientmentioning
confidence: 95%
“…These difficulties led to the design of a two-phase partitioning bioscrubber (TPPB) in which aqueous and organic phases were completely mixed as a single homogenous phase [7,8]. We have recently shown the potential of replacing the liquid organic phase of TPPBs with inexpensive polymers as a second phase, which has the advantage of allowing the use of microbial consortia, while also eliminating operational challenges (e.g., emulsions) which sometimes arise in two-liquid phase TPPBs [9].…”
Section: Introductionmentioning
confidence: 99%
“…A schematic of the airlift SL-TPPB used by Littlejohns and Daugulis,3 which is modeled in the current study, can be seen in Fig. 1.…”
Section: System Descriptionmentioning
confidence: 99%
“…3 Performance indicators (removal efficiency and elimination capacity) were predicted over various loadings and inlet gas flow rates. An estimability analysis of model parameters was completed in order to identify the parameters to which output is most sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…Silicone oil has been found to be the best second phase for two-phase partitioning bioreactors [1]. Littlejohns and Daugulis [4] reported a 30% increase in removal efficiency of BETX from air after inclusion of silicone oil (10%, v/v). Arriaga et al [5] reported large improvement in the elimination capacity of a biofilter after use of silicone oil.…”
Section: Introductionmentioning
confidence: 99%